Language creativity a semiotic perspective - Casini, Simone, 1982- (Lexington Books, 2020)
"This book considers the concept of linguistic creativity in relation to contact languages and language educational. The perspective proposed places semiotic creativity to the rank of first principle, by which languages are defined, function, and interact"--